Immunoadjunctive Therapy against Bacterial Infections Using Herbal Medicines Based on Th17 Cell-mediated Protective Immunity - Tomioka, Haruaki; Tatano, Yutaka; Shimizu, Toshiaki; Sano, Chiaki (Current Pharmaceutical Design, 2021)
One of the major health concerns in the world is the global increase in intractable bacterial infectious diseases due to the emergence of multi- and extensively drug-resistant bacterial pathogens as well as increase in compromised hosts around the world. Particularly, in the case of mycobacteriosis, the high incidence of tuberculosis in developing countries, resurgence of tuberculosis in industrialized countries, and increase in the prevalence of Mycobacterium avium complex infections are important worldwide health concerns. However, the development of novel antimycobacterial drugs is currently making slow progress. Therefore, it is considered that devising improved administration protocols for clinical treatment against refractory mycobacteriosis using existing chemotherapeutics is more practical than awaiting the development of new antimycobacterial drugs. The regulation of host immune responses using immunoadjunctive agents may increase the efficacy of antimicrobial treatment against mycobacteriosis. The same situations also exist in cases of intractable infectious diseases due to common bacteria other than mycobacteria. The mild and long-term up-regulation of host immune reactions in hosts with intractable chronic bacterial infections, using herbal medicines and medicinal plants, may be beneficial for such immunoadjunctive therapy. This review describes the current status regarding basic and clinical studies on therapeutic regimens using herbal medicines, useful for the clinical treatment of patients with intractable bacterial infections. In particular, we focus on immunoadjunctive effects of herbal medicines on the establishment and manifestation of host antibacterial immunity related to the immunological roles of Th17 cell lineages.
Keywords: Th17 cells